Community Empowerment in Kasunyatan Village Through the Utilization of Water Hyacinth (Eichhornia crassipes) into Biomass Briquettes as an Effort for Flood Mitigation and Local Economic Improvement - Mudmainah Vitasari; Tauny Akbari; Enggar Utari; Ika Rifqiawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The water hyacinth problem in the Cibanten River has not been optimally addressed. Community efforts, along with the Youth Organization (Karang Taruna) and the Maulana Yusuf Tourism Awareness Group (POKDARWIS), have generally been limited to river cleanups and community service activities. These activities are temporary, as the water hyacinth will regrow within a short time. However, if managed properly, water hyacinth has significant potential as a biomass resource that can be utilized to create valuable and economically viable products, one of which is biomass briquettes. Community empowerment activities in Kasunyatan Village, utilizing water hyacinth to produce biomass briquettes, have achieved their objectives. The community has successfully increased their knowledge, skills, and awareness of sustainable environmental management. The participatory, case-based implementation method is aligned with the challenges and needs of the community facing flooding and excessive water hyacinth growth. This program has had a positive impact on the environment by reducing river blockages and providing economic benefits through business opportunities for briquette production. Furthermore, it has fostered collective community awareness to maintain environmental cleanliness and utilize local resources independently. In the future, it is recommended that this activity be developed by improving the quality of briquette products and strengthening cooperation with related parties to provide broader and more sustainable benefits.